Genetic Diversity of Parkia biglobosa from Different Agroecological Zones of Nigeria Using RAPD Markers. (6th November 2014) - Amusa, Oluwafemi; Adesoye, Adenubi; Ogunkanmi, Adebayo; Omoche, Ojobo; Olowe, Olumayowa; Akinyosoye, Solomon; Omodele, Taiwo
Abstract : Parkia biglobosa (Jacq.) is an important leguminous tree crop in the African Savannahs useful to the natives where it is found, for domestic use. Previous diversity studies on this tree crop had been majorly on morphological and biochemical analysis. In order to capture the maximum diversity not obtained by previous research, the study aimed at evaluating the genetic diversity of accessions of this crop in the different agroecological zones in Nigeria using RAPD markers. A total of 81 scorable bands with an average of 8.1 bands per primer were amplified among the accessions studied. Intrazonal genetic diversity analysis showed a percentage polymorphism with a range of 11.11% to 65.43% among the agroecological zones studied. Although, gene diversity was highest within Humid forest agroecological zone, a low genetic distance and high genetic similarity between the agroecological zones were observed. Cluster analysis indicated six main groups of which four groups had single accessions while the two groups clustered the remaining accessions, indicating a narrowed genetic base from the 23 accessions studied.